2020
DOI: 10.21203/rs.3.rs-35068/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal fluid levels of amyloid-beta oligomers in patients with idiopathic normal pressure hydrocephalus are elevated before shunt surgery but decrease afterward

Abstract: Background The amyloid-beta (Aβ) oligomer has strong neurotoxicity and is associated with cognitive impairment in Alzheimer’s disease (AD). However, its role in patients with idiopathic normal pressure hydrocephalus (iNPH) is poorly understood. We hypothesised that cerebrospinal fluid (CSF) stagnation leads to Aβ oligomer accumulation in patients with iNPH. We measured CSF Aβ oligomer levels before and after CSF shunting in patients with iNPH. Methods We evaluated two iNPH cohorts: an analysis cohort (cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…However, elucidating cognitive changes over a longer-term course or in cases of iNPH with comorbid diseases is a challenge for iNPH treatment selection. It has been reported that CSF biomarkers are useful to differentiate patients with iNPH with comorbid neurodegenerative diseases and that patients with Alzheimer's disease are less likely to have their cognitive function improved ( 37 44 ). We believe that in the present cohort, the multicenter study (SINPHONI-1 and SINPHONI-2) may include selection bias that recruited iNPH without comorbidities as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…However, elucidating cognitive changes over a longer-term course or in cases of iNPH with comorbid diseases is a challenge for iNPH treatment selection. It has been reported that CSF biomarkers are useful to differentiate patients with iNPH with comorbid neurodegenerative diseases and that patients with Alzheimer's disease are less likely to have their cognitive function improved ( 37 44 ). We believe that in the present cohort, the multicenter study (SINPHONI-1 and SINPHONI-2) may include selection bias that recruited iNPH without comorbidities as much as possible.…”
Section: Discussionmentioning
confidence: 99%